Rates of switching to second-line antiretroviral therapy and impact of delayed switching on immunologic, virologic, and mortality outcomes among HIV-infected adults with virologic failure in Rakai, Uganda - Ssempijja, Victor (BMC Infect Dis, 2017)
BACKGROUND: Switch from first to second-line ART is recommended by WHO for patients with virologic failure. Delays in switching may contribute to accumulated drug resistance, advanced immunosuppression, increased morbidity and mortality. The 3rd 90′ of UNAIDS 90:90:90 targets 90% viral suppression for persons on ART. We evaluated the rate of switching to second-line antiretroviral therapy (ART), and the impact of delayed switching on immunologic, virologic, and mortality outcomes in the Rakai Health Sciences Program (RHSP) Clinical Cohort Study which started providing ART in 2004 and implemented 6 monthly routine virologic monitoring beginning in 2005. METHODS: Retrospective cohort study of HIV-infected adults on first-line ART who had two consecutive viral loads (VLs) >1000 copies/ml after 6 months on ART between June 2004 and June 2011 was studied for switching to second-line ART. Immunologic decline after virologic failure was defined as decrease in CD4 count of ≥50 cells/ul and virologic increase was defined as increase of 0.5 log 10 copies/ml. Competing risk models were used to summarize rates of switching to second-line ART while cox proportional hazard marginal structural models were used to assess the risk of virologic increase or immunologic decline associated with delay to switch first line ART failing patients. RESULTS: The cumulative incidence of switching at 6, 12, and 24 months following virologic failure were 30.2%, 44.6%, and 65.0%, respectively. The switching rate was increased with higher VL at the time of virologic failure; compared to those with VLs ≤ 5000 copies/ml, patients with VLs = 5001–10,000 copies/ml had an aHR = 1.81 (95% CI = 0.9–3.6), and patients with VLs > 10,000 copies/ml had an aHR = 3.38 (95%CI = 1.9–6.2). The switching rate was also increased with CD4 < 100 cells/ul at ART initiation, compared to those with CD4 ≥ 100 cells/ul (aHR = 2.30, 95% CI = 1.5–3.6). Mortality in patients not switched to second-line ART was 11.9%, compared to 1.2% for those who switched (p = 0.009). Patients switched after 12 months of of virologic failure were more likely to experience CD4 decline and/or further VL increases. CONCLUSIONS: Intervention strategies that aid clinicians to promptly switch patients to second-line ART as soon as virologic failure on 1st line ART is confirmed should be prioritized. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12879-017-2680-6) contains supplementary material, which is available to authorized users.